A Qualitative Case Study on Teachers' Identities, Ideologies, and Commitment to Teach in Urban and Suburban Schools - (:unkn) unknown (My University, 2013)
Using narrative inquiry, this study employed a Critical Race Theory lens to examine the ways in which identity factors such as race, culture, socioeconomic status, and gender work in concession with teachers' ideologies, as demonstrated by their values, beliefs, and perceptions about race, to inform their teaching practices, experiences with students and families of color, and commitment to teach. The main question this research study sought to examine was: How do teachers' identities and ideologies, as demonstrated by their values, beliefs, and perceptions, influence their decisions to remain in or leave urban and suburban classrooms? The study focused on the lived experiences of four teachers, 2 whom taught in urban schools and 2 whom taught in suburban schools. Based on the findings of this study, it is my contention that the ideologies espoused by my four participants all evolved from a source of pain, rooted in their identities and their experiences living in a racialized country. The ways in which they reacted, however, made all the difference. Each of the women's identity and their experiences with race, had a direct impact on their ideologies and the ways in which they interacted with their students. At times their experiences led them to operate from an activist stance, rendering them powerful, while at other times, their experiences caused them to function from a source of pain, thus rendering them powerless. The following four recommendations were derived based on the findings of this study: the need for teachers to develop a clearer understanding with regard to the historical underpinnings, permanence and pervasiveness of racism in America; the need for teachers to become self-reflective about their identities and the ways it relates to privilege and whiteness; the need for teachers to develop a critical consciousness and seek alternative ways of understanding the world, particularly from the paradigms of the marginalized and oppressed; and the need for teachers, particularly teachers of color to continue to challenge majoritarian tales and forge alliances with White teachers who are committed to participating in the fight for equity.
Keywords: Critical Race Theory; Race; Students of Color; Teachers' Identities; Teachers' Ideologies; Urban Schools